COMPARATIVE STUDY OF DIFFERENT FORMS OF MATERIAL PROCUREMENT WITH RESPECT TO THE LOGISTIC AND PURCHASING ACTIVITIES OF THE MANUFACTURING COMPANY (Perner's Contacts, 2011)
The contribution brings an insight into the different forms of material procurement. It compares so-called traditional approach of procurement with Just-in-Time and Just-in-Sequence approaches and points out main characteristics of each system with respect to logistic and purchasing activities